Cosmological Scalar Field ϕCDM Models - Avsajanishvili, Olga
Cosmological models that go beyond the standard Lambda Cold Dark Matter (ΛCDM) scenario, namely, scalar field ϕCDM models, are considered. The Hubble expansion rate of the universe, the dynamic and the energetic domination of dark energy, the formation of matter density fluctuations and the large-scale structure growth rate in these models compared to the standard spatially-flat ΛCDM model are investigated.
Keywords: Astronomy